Role of the Hippo pathway in autoimmune diseases - Hui Kong; Juan-Juan Han; Dmitrii Gorbachev; Xin-An Zhang (Experimental Gerontology, 2024)
The immune system is an important defense against diseases, and it is essential to maintain the homeostasis of the body's internal environment. Under normal physiological conditions, the steady state of the immune system should be sustained to play normal immune response and immune function. Exploring the molecular mechanism of maintaining immune homeostasis under physiological and pathological conditions will provides understanding of the pathogenesis of autoimmune diseases, infections, metabolic disorders, and tumors, as well as new ideas and molecular targets for the prevention and treatment of these diseases. Hippo signaling pathway can not only regulate immune cells such as macrophages, T cells and dendritic cells, but also interact with immune-related signaling pathways such as NF-kB signaling pathway, TGF-β signaling pathway and Toll-like receptor signaling pathway, so as to resist the internal environment disorder caused by the invasion of exogenous pathogenic microorganisms and maintain the internal environment stability and physiological balance of the body. Hippo signaling pathway is also involved in the pathological process of immune system-related diseases such as rheumatoid arthritis, inflammatory bowel disease and psoriasis. Hippo pathway is closely related to organ development, stem cell biology, regeneration, and tumor biology. It affects cell differentiation by participating in extracellular and intracellular physiological signal reactions, sensing cell environment, and coordinating cell reactions. This pathway is crucial in maintaining immune homeostasis. This review summarizes the mechanism of Hippo pathway in different immune cells and some autoimmune diseases and the interaction between different immune signaling pathways and Hippo signaling pathway. It aims to explore the role of Hippo in autoimmune diseases and provide theoretical and practical basis for the treatment of autoimmune diseases through Hippo signaling pathway.